Effects of voriconazole and fluconazole on the pharmacokinetics of almonertinib in rats by UPLC–MS/MS. (27th October 2022) - Fu, Yuhao; Li, Ying; Ma, Yinling; He, Xueru; Xun, Xuejiao; Cui, Yanjun; Fan, Liju; Dong, Zhanjun
Abstract: Almonertinib was included in the first‐line treatment of non‐small cell lung cancer with EGFR T790M mutations by the Chinese Society of Clinical Oncology in 2021. Considering that immunocompromised lung cancer patients are prone to opportunistic fungal infections, and most triazole antifungal drugs are moderate or strong inhibitors of CYP3A4, this study was conducted to develop and validate an accurate and rapid ultra‐performance liquid chromatography tandem mass spectrometry method for quantifying almonertinib in plasma and for investigating the pharmacokinetic changes of almonertinib caused by voriconazole and fluconazole in rats. After liquid–liquid extraction with tert ‐butyl methyl ether, an XSelect HSS T3 column (2.1 × 100 mm, 2.5 μm, Waters) was used for the chromatographic separation of almonertinib and sorafenib‐D3 (internal standard). The analytes were detected using an AB Sciex Triple Quad 5, 500 mass spectrometer in the positive ionization mode. The method exhibited great linearity (0.5–200 ng/ml, r > 0.997) and stability under the established experimental conditions. All validation experiments were in accordance with the guidelines, and the results were all within the acceptable limits. This method was successfully applied to the researches of pharmacokinetics and drug interactions for almonertinib in rats. Voriconazole and fluconazole significantly altered the pharmacokinetic profiles of almonertinib and increased the systemic exposure of almonertinib in rats to different degrees, but further human trials should be conducted to validate the results.